To multiply (7–√) and (-2–√), we can use the FOIL method.
(7–√) (−2–√) = 7(-2) + 7(-√) + (-√)(-2) + (-√)(-√)
Simplifying, we get:
= -14 - 7√ - 2√ + √²
Since √² is equal to the square root of 1, we have:
= -14 - 9√ + 1
Combining like terms, we get:
= -13 - 9√
Multiply and Divide Radicals Quick Check 1 of 51 of 5 Items Question Multiply (7–√) (−2–√) . Give an exact answer.(1 point) Responses 14−−√ s
tart root 14 end root 5–√
start root 5 end root −14−−√
negative start root 14 end root −72–√
1 answer